Development and Validation of In Vitro Assessment Protocol of Novel Intravenous Nanoemulsions for Parenteral Nutrition - Joanna Czerniel; Aleksandra Gostyńska-Stawna; Karina Sommerfeld-Klatta; Tomasz Przybylski; Violetta Krajka-Kuźniak; Maciej Stawny (Pharmaceutics)
Background: Parenteral nutrition (PN) is a lifesaving therapeutic approach for patients unable to meet nutritional needs through oral or enteral routes. Lipid nanoemulsions (NEs), a critical component of PN, provide essential fatty acids and influence the formulation’s physicochemical properties. Advances in drug delivery systems have led to novel intravenous NEs with improved stability, purity, or ability for nutrient/active substance delivery. Due to scattered information and the lack of a standardized protocol for testing intravenous lipid NEs, this study aimed to develop a robust assessment method. The protocol focuses on characterizing the physicochemical properties, stability, and biological efficacy of novel NEs while adhering to bioethical standards. Methods: Four NEs were formulated based on fatty acid profile analysis, and to demonstrate the applicability of our protocol, each NE utilized a distinct emulsifier system. A comprehensive in vitro assessment protocol integrating multiple analytical techniques was employed to evaluate their performance. Results: The mean droplet diameter (MDD) of developed NEs ranged from 180.7 to 185.9 nm, significantly smaller than commercial formulations (249.6–335.4 nm). PFAT5 remained below 0.02%, except for ILE-HS (0.12%), and the zeta potential (ZP) was below −29.8 mV. The freeze–thaw stability constant (KF) of developed NEs was in the range of commercial formulation, and the sterilization stability constant (KS) was below 10, except for ILE-HS (23.61 ± 1.65). Injectability tests confirmed that ILE-ELP and ILE-T could be infused at 50 mL/h using an intravenous access with a minimum diameter of 21 G. Hemolytic activity met the strictest criteria (<5%), and MTT assays showed higher cell viability at low concentrations for all NEs except ILE-ELP. Conclusions: The developed five-step protocol provides a unified framework for assessing intravenous lipid NEs, allowing for the selection of NEs with the highest potential for further in vivo assessment.